Effect of semolina pudding prepared from starch branching enzyme IIa and b mutant wheat on glycaemic response in vitro and in vivo: a randomised controlled pilot study. Issue 1 (20th December 2019) - Corrado, Marina; Cherta-Murillo, Anna; Chambers, Edward S.; Wood, Abigail J.; Plummer, Amy; Lovegrove, Alison; Edwards, Cathrina H.; Frost, Gary S.; Hazard, Brittany A.
Abstract : The starch characteristics of raw semolina determine sbeIIa / b -AB pudding digestibility in vitro and glycaemic index in vivo . Abstract : Refined starchy foods are usually rapidly digested, leading to poor glycaemic control, but not all starchy foods are the same. Complex carbohydrates like resistant starch (RS) have been shown to reduce the metabolic risk factors for chronic diseases such as hyperglycaemia and overweight. The aim of the project was to develop a semolina-based food made from a starch branching enzyme II ( sbeIIa / b -AB) durum wheat mutant with a high RS content and to measure its glycaemic index using a double-blind randomised pilot study. We report here the amylose, RS and non-starch polysaccharide concentration of raw sbeIIa / b -AB and wild-type control (WT) semolina. We measured RS after cooking to identify a model food for in vivo testing. Retrograded sbeIIa / b -AB semolina showed a higher RS concentration than the WT control (RS = 4.87 ± 0.6 g per 100 g, 0.77 ± 0.34 g per 100 g starch DWB, respectively), so pudding was selected as the test food. Ten healthy participants consumed ∼50 g of total starch from WT and sbeIIa / b -AB pudding and a standard glucose drink. Capillary blood glucose concentrations were measured in the fasting and postprandial state (2 h): incremental area-under-the-curve (iAUC) and GI were calculated. We found no evidence of difference in GI between sbeIIa / b -AB pudding and the WT control, but the starch digestibility was significantly lower in sbeIIa / b -AB pudding compared to the WT control in vitro ( C 90 = 33.29% and 47.38%, respectively). Based on these results, novel sbeIIa / b -AB wheat foods will be used in future in vivo studies to test the effect of different RS concentrations and different food matrices on glycaemia.